DELLA proteins regulate expression of a subset of AM symbiosis-induced genes in Medicago truncatula - Floss, Daniela S. (Plant Signal Behav, 2016)
The majority of the vascular flowering plants form symbiotic associations with fungi from the phylum Glomeromycota through which both partners gain access to nutrients, either mineral nutrients in the case of the plant, or carbon, in the case of the fungus.(1) The association develops in the roots and requires substantial remodeling of the root cortical cells where branched fungal hyphae, called arbuscules, are housed in a new membrane-bound apoplastic compartment.(2) Nutrient exchange between the symbionts occurs over this interface and its development and maintenance is critical for symbiosis. Previously, we showed that DELLA proteins, which are well known as repressors of gibberellic acid signaling, also regulate development of AM symbiosis and are necessary to enable arbuscule development.(3) Furthermore, constitutive overexpression of a dominant DELLA protein (della1-Δ18) is sufficient to induce transcripts of several AM symbiosis-induced genes, even in the absence of the fungal symbiont.(4) Here we further extend this approach and identify AM symbiosis genes that respond transcriptionally to constitutive expression of a dominant DELLA protein and also genes that do respond to this treatment. Additionally, we demonstrate that DELLAs interact with REQUIRED FOR ARBUSCULE DEVELOPMENT 1 (RAD1) which further extends our knowledge of GRAS factor complexes that have the potential to regulate gene expression during AM symbiosis.